2, 4, 6‐Triphenyl‐1, 3, 5‐Triazine Based Covalent Organic Frameworks for Photoelectrochemical H2 Evolution. Issue 7 (16th February 2021) - Dai, Chunhui; He, Ting; Zhong, Lixiang; Liu, Xingang; Zhen, Wenlong; Xue, Can; Li, Shuzhou; Jiang, Donglin; Liu, Bin
Abstract: Photoelectrochemical water splitting over semiconductors offers a sustainable solar light conversion technique capable of alleviating worldwide energy crisis. Conjugated polymers have recently received increasing attention as a class of promising photoelectrode materials due to their advantages of earth‐abundance, non‐toxicity, light weight, and molecularly tunable functionalities, etc. However, the development of highly efficient organic photoelectrodes remains a big challenge. In this study, two covalent organic frameworks (COFs) incorporated 2, 4, 6‐triphenyl‐1, 3, 5‐triazine are demonstrated as excellent photocathodes for H2 production. By introducing 2, 4, 6‐triphenylbenene to properly create donor/acceptor pairs within COF, a significantly enhanced visible‐light photocurrent of TAPB‐TTB COF (110 µA cm −2 ) compared to TTA‐TTB COF (35 µA cm −2 ) at 0 V versus reversible hydrogen electrode (RHE) is obtained without adding organic sacrificial agent and metal cocatalysts (>420 nm). The enhanced photocurrent density is attributed to the narrowed bandgap and improved charge transfer by intramolecular donor–acceptor combination. This work highlights the great promising applications of crystalline donor–acceptor COFs as high‐efficiency organic photoelectrode for water splitting. Abstract : Two 2, 4, 6‐triphenyl‐1, 3, 5‐triazine based COFs are studied as highly efficient photoelectrodes for hydrogen production under visible light. This work demonstrates how comonomers in 2D COFs with intramolecular donor‐acceptor system can be tuned to achieve synergetic interactions for PEC water splitting, thereby providing the basis for designing new organic photoelectrode.